Further Application of Bomb 14 C as a Tracer in the Atmosphere and Ocean - Nydal, Reidar; Gislefoss, Jorunn S. (Radiocarbon, 1996)
Bomb 14 C from nuclear tests in the atmosphere has proved to be a particularly useful tool in the study of the carbon cycle. We provide here a ca. 30-yr time series of 14 C concentrations in the atmosphere between 28°N and 71°N and in the ocean surface between 45°S and 45°N. More recently (since 1990), a north-south profile also has been obtained for 14 C in the surface waters of the Atlantic Ocean. The measurements were performed using the conventional technique of beta counting or large samples (4 to 5 liter CO 2 ) in CO 2 proportional counters. These data show that the 14 C concentration in the atmosphere is leveling off with a time constant of 0.055 yr -1 , and is now approaching that of the ocean surface at lower latitudes. Additional tracer studies have been concerned especially with the penetration of bomb 14 C into the deep ocean. The Norwegian and Greenland seas are of interest as a sink for atmospheric CO 2 and also a source of water for the deep Atlantic Ocean. During the last five years, several 14 C depth profiles have been measured from the Fram Strait (79°N) to south of Iceland (62°N), using the AMS technique available at the University of Arizona AMS Facility. We considered it important to repeat and compare a few of the profiles with those produced by the GEOSECS expedition in 1972 and the TTO expedition in 1981. The profiles show that water descending to the deep Atlantic Ocean is originating mainly from intermediate and surface depths in the Nordic Seas. However, the ventilation rate of the Norwegian Sea deepwater is too slow to be an important component in the transfer of water over the Greenland-Scotland Ridge.